Effect of an hydrophobic layer on a universal adhesive - Mayara Farah Dallin SERAFIM; Adriana Mara Araújo LEAL; José BAUER; Isabella Azevedo GOMES; Karina Gama Kato CARNEIRO (Faculdade São Leopoldo Mandic, 2018)
Objective: evaluate bond strength of a universal adhesive, associated to an extra hydrophobic sealing layer, and compare after three and six months immersed in distilled water. Methods: After ethical approval of the CEP / HUUFMA, 12 human third molars (n = 6) were extracted, which were divided into two groups: SB - control group - selfetching; and SBHidrof - selfetching group associated to the hydrophobic layer (Adhesive layer, 3m ESPE). After incremental restoration with composite resin (Opalis, FGM), the teeth were sliced to obtain specimens (1mm2) and then submitted to the universal test machine (INSTRON 1mm / min.), immediate and after three and six months. The data were submitted to normality (Shapiro Wilk), and comparative Analysis of variance (two ways: technique and time) and Tukey (p <0.05). Results Immediate values showed no statistically significant difference (p> 0.05), but after three and six months of immersion of the specimens, in distilled water, bond strength values were maintained in the group that received the hydrophobic layer (p<0.05). Conclusion: It was observed that, by incorporating a hydrophobic layer on a universal adhesive system, it was possible to preserve dentin adhesion.